SEMANGAT PEMBAHARUAN DAN PENEGAKAN HUKUM INDONESIA DALAM PERSPEKTIF SOCIOLOGICAL JURISPRUDENCE - Muhammad Junaidi (UNISSULA, 2016)
The spirit of renewal and law enforcement is often considered only based on a process of renewal and change the old Act to the new Act. If the renewal and law enforcement just conceived so, then the law will continue to be considered not present in the midst of society as part of the settlement of the problem. As a solution needs to be established is to integrate the spirit of renewal and law enforcement collaborated with social reality. Thus the ideal model is expected become law unifying identity as an expression of popular sovereignty and the pattern of State laws harmonization purposes.